2018
DOI: 10.3390/ijerph15092016
|View full text |Cite
|
Sign up to set email alerts
|

Food Insecurity and Cardiovascular Disease Risk Factors among Mississippi Adults

Abstract: Background: Food insecurity is a public health problem. There is limited data on food insecurity in Mississippi. Methods: We analyzed data from the 2015 Mississippi Behavioral Risk Factor Surveillance System, which included the Social Context Module for 5870 respondents. Respondents who indicated that in the past 12 months they were “always”, “usually”, or “sometimes” “worried or stressed about having enough money to buy nutritious meals” were considered food insecure. Food insecurity was compared across socio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 17 publications
1
45
0
2
Order By: Relevance
“…Additionally, 47.86% of 2017 high school graduates in Mississippi who went on to enroll in an in-state community college within 16 months of graduation were classified as economically disadvantaged, and 14.72% of graduates who went on to enroll in an in-state four-year public university were economically disadvantaged [30]. Lastly, data from the 2015 Mississippi Behavioral Risk Factor Surveillance System found that two out of every five Mississippi adults are food insecure, which further indicates the likelihood of food insecurity rates in college students being higher than average state-wide [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, 47.86% of 2017 high school graduates in Mississippi who went on to enroll in an in-state community college within 16 months of graduation were classified as economically disadvantaged, and 14.72% of graduates who went on to enroll in an in-state four-year public university were economically disadvantaged [30]. Lastly, data from the 2015 Mississippi Behavioral Risk Factor Surveillance System found that two out of every five Mississippi adults are food insecure, which further indicates the likelihood of food insecurity rates in college students being higher than average state-wide [17].…”
Section: Discussionmentioning
confidence: 99%
“…African American and Hispanic headed households have greater than average rates of food insecurity [3] and are also at a greater risk for type 2 diabetes [13], hypertension [14], and cardiovascular disease [15]. Looking at Mississippi, the state's African American population has the highest mortality rate due to heart disease, hypertension, stroke, and diabetes [16], in addition to having a significantly greater prevalence of food insecurity compared to Mississippi's Caucasian population [17]. These data consistently demonstrate that food insecurity, race, and health outcomes are all closely related.…”
Section: Introductionmentioning
confidence: 99%
“…43,44 As of 2016, 12% of Utah residents reported being food insecure, which is near the national average of 13%. 2,45 Our findings indicate that even in a state with average levels of food insecurity, striking disparities may be present in subgroups as the rate of food insecurity in our sample was 30%.…”
Section: Discussionmentioning
confidence: 59%
“…A amostra aleatória estratificada foi constituída por 719 usuários dos serviços de saúde, sendo 512 (71,2%) do sexo feminino e 207 (28,8%) do sexo masculino (MENDY et al, 2018;PAN et al, 2012).…”
Section: Amostra Do Estudounclassified
“…Os 10 passos da alimentação saudável para adultos também foram utilizados para análise em outros estudos no cenário nacional e internacional (MARATOYA et al, 2013;GOMES;SOARES;GONÇALVES, 2016;COELHO et al, 2017;MENDY et al 2018;BERNAL;OLIVEIRA, 2015;BOREK et al, 2017).…”
Section: Caracterização Dos Participantes Segundo As Variáveis Refereunclassified